Effectiveness of Forensic Auditing on Fighting Fraud Among Non-Government Organisations in South Africa - Jean Damascene MVUNABANDI (Indonesia Strategic Sustainability, 2023)
This article sought to empirically establish the effectiveness of proactive forensic auditing techniques for 30 non-government organisations in the eThekwini region, South Africa. This article adopted quantitative and descriptive survey research. The data for this research was gathered via the use of the quantitative research method through an online questionnaire which was designed in a 5-point Likert scale and used for data analysis. Robustness analysis was entirely performed using SPSS software version 27 for statistical analysis. The study’s results showed that there exists a positive statistically significant relationship between the applicability of forensic auditing techniques and fraud detection, prevention and investigation among non-government organisations in the eThekwini region, South Africa. It also found that the application of forensic auditing techniques has its highest applications in proactive fraud detection. Based on the above, it was recommended that the application of forensic auditing skills and techniques among non-government organisations should be considered carefully.